Making clear teachers' experience-led wisdom in the context of teaching practicum: a conceptual and methodological framework - Gervais, Colette; Correa Molina, Enrique (Íkala, Revista de Lenguaje y Cultura, 2004)
Teachers lack the appropriate tools to acurately express their practice in words. It is important to illustrate and communicate the knowledge used in the practice of teaching to give access to the experience. This article presents the conceptual and methodological framework of a study inspired by the practical argumentation approach, and the analysis of the teaching practice of the participants by means of shared thoughts as well as the analysis of video recordings. Receved: 08 –06-04/ Accepted: 25/08/04 How to reference this article: Gervais, C. & Correa Molina, E. (2004). Explicitación del saber de experiencia de los profesores en el contexto de las prácticas docentes: un marco conceptual y metodológico. Íkala. 9(1), pp. 141 – 167